The Role Of Customer Satisfaction In Mediating The Influence Of Service Quality And Price On Customer Loyalty In Retail Companies - Setini, Made; januarianta, I Kadek; indiani, ni luh putu; Putra, Ida bagus udayana (International Journal of Management and Digital Business, 2025)
The retail sector has an important role in the economy, including in Klungkung Regency which shows rapid growth in the number of modern retailers. Fierce competition and shifting consumer behavior demand retail companies to focus on customer retention efforts. Customer loyalty is an important strategic asset for business sustainability, so a study of customer loyalty in the Klungkung retail sector needs to be carried out. This study aims to analyze the influence of service quality and price on customer loyalty with customer satisfaction as a mediating variable in retail companies in Klungkung Regency.The population of this study is all consumers who shop at retail companies in Klungkung Regency. The sample used was 102 respondents from consumers in retail companies in Klungkung Regency. The data collection method is to use a survey ketode with a questionnaire as a research instrument. The analysis technique used to answer the hypothesis is inferential statistical analysis using Partial Least Square (PLS). The results of the study found that service quality has a significant positive effect on customer loyalty, price has a significant positive effect on customer loyalty, service quality has a significant positive effect on customer satisfaction, price has a significant positive effect on customer satisfaction, customer satisfaction has a significant positive effect on customer loyalty, customer satisfaction is able to mediate part of the relationship between service quality and customer satisfaction. customer loyalty, and customer satisfaction are able to mediate part of the price relationship to customer loyalty in retail companies in Klungkung Regency.